Orthodontic Retention Protocols: Evaluating the Effectiveness of Different Retention Protocols in Maintaining Post-Treatment Tooth Alignment - Snigdha Pattanaik; Vishnu Priya Veeraraghavan; Arun Kumar Dasari; Kaladhar Reddy Aileni; Santosh Rayagouda Patil (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the effectiveness of various orthodontic retention protocols, including removable retainers, fixed retainers, and a combination of both. Material and Methods: A cohort of orthodontic patients (n=240) was divided into four groups: Removable Retainer Group, Fixed Retainer Group, Combination Protocol Group, and Control Group. Tooth alignment stability, patient satisfaction, compliance, and adverse event occurrence were assessed over two years. Data analysis included regression analysis and comparisons between groups. Results: Fixed retainers demonstrated superior effectiveness in maintaining tooth alignment stability compared to removable retainers and the combination protocol, with the slightest deviation from baseline alignment. The Fixed Retainer Group also reported the highest patient satisfaction and compliance rates. Adverse events and complications, such as retainer breakage and discomfort, were more frequent in the Removable Retainer Group. Conclusion: Fixed retainers offer superior tooth alignment stability, patient satisfaction, and compliance, while adverse events are relatively infrequent and manageable. However, patient preferences and needs should be considered when choosing the most appropriate retention strategy.